Ускользающее "Я" или кризис идентичности - Дышкант, Татьяна Николаевна (Харківський національний університет ім. В. Н. Каразіна, 2019)
В статье рассматриваются проблемы индивидуального и родового самоопределения человека в связи с угрозами, содержащимися в явлениях, продуцируемых информационным обществом и тиражируемой им массовой культурой и приводящим к внутренней дисгармонии, фрагментарности личности, что может обернуться ложной идентификацией.

At the present stage of development of society the problem of identification and self- identification of the person becomes actual one. Individual consciousness is split by the influence of mass culture, the use of technologies of consciousness change, for example, in situations of formation of public opinion, the absolutization of any facet of a person (a person who produces, a person who consumes, etc.). The problem of self-identification without understanding the essence of man cannot be solved.
The elusive "I" or an identity crisis
Keywords: сознание; постмодернизм; массовая культура; самоидентификация; identity; consciousness; postmodernism; mass culture